The Impact of High School Financial Education Experimental Evidence from Brazil - Bruhn, Miriam (The World Bank, 2013)
This paper studies the impact of a comprehensive financial education program spanning six states, 868 schools, and approximately 20,000 high school students in Brazil through a randomized control trial. The program increased student financial knowledge by a quarter of a standard deviation and led to a 1.4 percentage point increase in saving for purchases, better likelihood of financial planning, and greater participation in household financial decisions by students. "Trickle-up" impacts on parents were also significant, with improvements in parent financial knowledge, savings, and spending behavior. The study also finds evidence that the program affected students' inter-temporal preferences and attitudes